Restriction of constitutional rights and freedoms by Iraq's cabinet government in handling Covid-19 - Mohsin, Zahraa Abdulalhafudh (Otoritas : Jurnal Ilmu Pemerintahan, 2024)
This study investigates the constitutional legitimacy of the measures enacted by Tthe Iraqi government to prevent the COVID-19 spreading, which restricted the rights and freedoms enshrined in the Iraqi Constitution 2005. even though the epidemic is a health emergency, the House of Representatives has not declared an emergency state, as the Cabinet resorted to taking preventive measurement to curb the crisis spreading, that restricted constitutional freedoms and rights even though the Iraqi constitution explicitly states that the rights and freedoms cannot be restricted except by law or based on it,  however, this restriction was governed by administrative orders issued by a committee establish by council of ministers under  Diwani Order 55 of 2020, headed by the minister of health,  which  amended then to become headed by the prime minister, for that purpose we have followed the analytical approach to assess the decisions taken by this committee through interpreting constitutional and legal texts and examining many of their restrictive resolutions imposed for demonstrating its legitimacy or illegitimacy and through this analysis we concluded that the majority of its decision on rights and freedoms under the pretext to preventspread  of Covid-19 unconstitution even though the epidemi was serious it cannot be justified  for violating democratic values.